1995
DOI: 10.4141/cjas95-046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deoxynivalenol-contaminated diet on performance and blood parameters in growing swine

Abstract: 1995. Effects of deoxynivalenol-contaminated diet on performance and blood parameters in growing swine. Can. J. . An experiment was conducted to determine the effects of feeding a deoxynivatenot (lON)-contaminated diet (4.0 mg DON kg-1 dieg on performance and blood parameters of growing pigs 1tS.O-SO.S tg body weight) over a42-dperiod. Blood simples were collected weekly from all animals. Ad libitum fed control and pair-fed control groups were used to distinguish between differences in feed intake and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…Vesonder et al (1973) first identified DON as the mycotoxin responsible for anorexia and emesis in swine consuming Fusarium-contaminated corn. Since then, several investigators have examined the relationship between the level of DON in the diet and the resultant impact on feed intake in swine (Young et al 1983;Cote et al, 1985;Pollman et al 1985;Chavez and Rheaume 1986;Friend et al 1986a,b;Rotter et al 1995;Smith et al 1997). In general, these groups found a reduction of 4-8% in feed intake, relative to DON-free controls, for every 1 ppm of DON.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesonder et al (1973) first identified DON as the mycotoxin responsible for anorexia and emesis in swine consuming Fusarium-contaminated corn. Since then, several investigators have examined the relationship between the level of DON in the diet and the resultant impact on feed intake in swine (Young et al 1983;Cote et al, 1985;Pollman et al 1985;Chavez and Rheaume 1986;Friend et al 1986a,b;Rotter et al 1995;Smith et al 1997). In general, these groups found a reduction of 4-8% in feed intake, relative to DON-free controls, for every 1 ppm of DON.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the final diets confirmed the absence of DON in the 0 ppm diet and the final DON levels in the treatment diets. Feed samples were also assayed for DON, 3 acetyl-DON and 15-acetyl-DON by electron-capture gas chromatography of the trimethylsilyl ether derivative (Scott et al 1989;Tacke and Casper 1996). The results indicated no 3-acetyl-DON or 15-acetyl-DON levels above the limits of detection of the assay (0.10 and 0.12 ppm, respectively).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Pair-feeding studies with pigs indicate that at the lower dose ranges, the effects of DON on growth may be explained entirely by the effects on voluntary feed intake (Rotter et al, 1995). However, Prelusky (1997) concluded that at relatively high dietary concentrations of DON (above 9 mg/kg), the deleterious effects on weight gain may not be fully explained by the Bergsjo et al (1992), Friend et al (1992), Bergsjo et al (1993), Prelusky et al (1994b), Trenholm et al (1994), and Rotter et al (1995).…”
Section: Feed Refusal Emesis and Anorexiamentioning
confidence: 99%
“…Deoxynivalenol, also known as vomitoxin, generally damages the digestive system of pigs causing vomiting or feed refusal (Trenholm et al, 1994) while ZON disturbs the reproductive system of female pigs and consequently reduces sow performance (Döll et al, 2003;Papatsiros, 2012). Some studies carried out the experiments using corn (Young et al, 1981;Rotter et al, 1995) or wheat (Friend et al, 1983;Waché et al, 2009) Science Publications AJAVS as a natural source of mycotoxin. However, there is limited information on the effects of DON and ZON in corn co-products contaminated by Fusarium fungi.…”
Section: Introductionmentioning
confidence: 99%